Patterns of Managerial Response as Organisations Move from Rich to Poor Environments - Pettigrew, A (1983)

(untitled)
Educational administrators facing change are offered some observations of business management, including an analysis of characteristic responses to change from rich to poor environments, a catalog of managerial styles likely to be discouraged or rewarded in present economic conditions, and recommended practices for managing contraction, especially by reducing fixed costs.